2018
DOI: 10.4244/eij-d-18-00461
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparison of healing response between the BuMA Supreme stent and the XIENCE stent at one-month and two-month follow-up: PIONEER-II OCT randomised controlled trial

Abstract: The aim of this study was to compare the strut coverage of the XIENCE stent with that of the BuMA Supreme sirolimus-eluting cobalt-chromium stent, which has a shorter drug elution, on optical coherence tomography (OCT) one or two months after implantation. Methods and results:The PIONEER-II OCT trial was a multicentre, two-arm randomised trial, which comprised two cohorts: cohort-1 underwent an OCT imaging one month after coronary intervention (BuMA: 16 patients with 18 lesions, XIENCE: 15 patients with 17 les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
4
15
1
1
Order By: Relevance
“…Interestingly, a recent report indicated that the BuMA SupremeÒ SES is associated with faster redevelopment of endothelial barrier function in rabbits than a durable polymer everolimus-eluting stent at the 45-and 90-day time points after stent implantation. 6 Although these findings appear consistent with our present observations, the precise relationship between these two sets of findings remains to be elucidated. In addition to the PBMA coating, the BuMA SupremeÒ SES also features a shorter drug release time than other DES.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, a recent report indicated that the BuMA SupremeÒ SES is associated with faster redevelopment of endothelial barrier function in rabbits than a durable polymer everolimus-eluting stent at the 45-and 90-day time points after stent implantation. 6 Although these findings appear consistent with our present observations, the precise relationship between these two sets of findings remains to be elucidated. In addition to the PBMA coating, the BuMA SupremeÒ SES also features a shorter drug release time than other DES.…”
Section: Discussionsupporting
confidence: 90%
“…Two particularly relevant recent studies in this regard used optical coherence tomography (OCT) measurements in a randomized trial to demonstrate that the BuMA SupremeÒ sirolimus-eluting stent (SES) (SINOMED, Tianjin, China) exhibits superior stent coverage in comparison to other widely-used drug-eluting stents such as the Xience V stent (Abbott Vascular). 6,23 In human postmortem histological analysis, strut coverage has been shown to be an independent predictor for late (> 30 days) stent thrombosis. 15 As depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mean neointimal hyperplasia was also calculated as a secondary assessment of strut and stent coverage. Outcomes were compared to values reported in the literature for populations with cardiovascular disease but without a cancer diagnosis (17)(18)(19)(20)(21)(22). Strut apposition and coverage were detected by whether the strut was located above, at, or below the lumen contour (Figure 1).…”
Section: Aims and Outcomes Of The Studymentioning
confidence: 99%
“…The impact of baseline characteristics and their association with stent healing are presented in Table 2. Stratified comparisons to literature values by follow-up duration of OCT after DES placement and stent brand (Resolute, Promus, and Xience stents) were performed with results noted in Table 3 (17)(18)(19)(20)(21)(22). For inclusion in a particular comparison, the follow-up duration of OCT needed to fall within the follow-up duration of stents included in the published study that generated a literature value.…”
Section: Strut and Stent Parametersmentioning
confidence: 99%
“…In the current issue of EuroIntervention, three reports (one case report 5 and two small size randomised clinical trials 6,7 ) examine the impacts of the aforementioned advances in the design of the metallic DES or BVS on vascular healing following stent/scaffold implantation, while a fourth observational study reports neointima patterns in the metallic DES >10 years after implantation 8 . All four studies use optical coherence tomography (OCT) to assess neointima morphology and utilise the presence of scaffold/strut coverage as surrogates for vascular healing post implantation.…”
mentioning
confidence: 99%